Contrasting the Effects of Task Difficulty and Perceptual Load on Auditory Detection Sensitivity in Individuals with Autism. - Tillmann, Julian; Swettenham, John (Journal of Autism & Developmental Disorders, 2019)
To test a central assumption of the increased perceptual capacity account in individuals with Autism Spectrum Disorder (ASD), the effects of perceptual load and target-stimulus degradation on auditory detection sensitivity were contrasted. Fourteen adolescents with ASD and 16 neurotypical controls performed a visual letter search task under three conditions: low perceptual load, high perceptual load and low perceptual load with a degraded target while simultaneously detecting an auditory tone in noise. For both participants with ASD and neurotypical controls, increasing perceptual load and target degradation increased task difficulty as indexed by reaction times and accuracy. However, only increasing perceptual load reduced subsequent auditory detection sensitivity. The study confirms that perceptual load, and not task difficulty, modulates selective attention in ASD.